British writers - Parini, Jay (Charles Scribner's Sons, 2012)
Peter Abbs – Brian Aldiss – Justin Cartwright – Michael Donaghy – Patrick Leigh Fermor – James Hanley – David Harsent – Shirley Hazzard – Elspeth Huxley – Mary Lavin – Sheridan Le Fanu – Patrick Leigh Fermor – Sorley MacLean – Nuala O'Faolain – Philippa Pearce – Adam Phillips – James Robertson – Charlotte Turner Smith – Meera Syal – Richard Chenevix Trench. Covers writers who have made significant contributions to British, Irish, and Commonwealth literature from the fourteenth century to the present day. Includes in-depth critical and biographical analysis
Description based on print version record
Keywords: English literature; Commonwealth literature (English); Authors; English; Authors; Commonwealth